DISPARITAS PEMBANGUNAN REGIONAL DALAM ERA DESENTRALISASI FISKAL: TINJAUAN LITERATUR TENTANG KONVERGENSI EKONOMI DAN EFEKTIVITAS INVESTASI PUBLIK DI INDONESIA - Ikhwan Alfiansyah (CV. Adiba Aisha Amira, 2026)
This study aims to examine regional development disparities in the era of fiscal decentralization through a systematic literature review focusing on economic convergence and the effectiveness of public investment in Indonesia. Fiscal decentralization is theoretically expected to promote equitable development by enhancing local government capacity in resource allocation. However, empirical evidence indicates that regional inequality remains persistent, driven by disparities in fiscal capacity, institutional quality, and uneven distribution of public investment. This study employs a library research approach by analyzing recent scholarly articles indexed in reputable databases over the last five years (2020–2025). The findings reveal that fiscal decentralization in Indonesia has produced mixed outcomes. While some regions demonstrate signs of β-convergence, overall regional disparities remain high, indicating the absence of consistent σ-convergence. Structural factors such as infrastructure gaps, market accessibility, and human capital inequality play significant roles in shaping these outcomes. Furthermore, public investment is identified as a crucial mediating variable in the relationship between fiscal decentralization and economic convergence. The effectiveness of such investment largely depends on governance quality, planning efficiency, and equitable allocation across regions. This study contributes to the literature by integrating fiscal decentralization, economic convergence, and public investment into a comprehensive analytical framework. It highlights the importance of strengthening institutional capacity and implementing equitable fiscal policies to achieve inclusive regional development. The findings have important policy implications for designing more effective decentralization strategies to reduce regional disparities and support sustainable economic growth in Indonesia.